(3JLGQH GdCee hJYGbH Gdgees - (3CHh Ydj CMeO Hf eMeO Hf eSchjgs
(3ChdgG (B:s
(3jHJOF (B( (3HHGH eG MaX ef cdGe GdCMfa hMV GdfGS Ydjg Hbhdg (B: (3Efg deG QLY ef YfO Ydi Ydjg GdSdGe dbjg gdGd Hf hcje hgh SjO QgWg abd eG QCjc ai ecGfg CejQ GdeDefjf s
(3BNQgG (B:s
(3Ke NQL (B( (3GdeNJGQ (B) (3ai JSYI YTQ QLdkG abGd GdfGS CJDefhfi hCNQL Ydjce abGdhG EdG GdCYdi GdMce abGd dG CMcece ai faSi CHOkG aVGQH HSjag MJi bJd fLR GdLRA GdKGfi ef cJGH JLGQH GdCee hjJdhg ai GdKGdK PcQ QCi GdeNJGQ ai Jdc GdCMhGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B344s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs